Pentingnya Merek Dan Kemasan Untuk Meningkatkan Daya Saing Produk Dari Usaha Mikro Dan Kecil - Ninuk Muljani; Arini Arini; Ani Suhartatik; Tuty Lindawati; P. Julius F. Nagel (LPPM, Universitas Katolik Widya Mandala Surabaya, 2020)
This community service aims to provide insights to micro and small entrepreneurs on the importance of brands and packaging to increase product competitiveness. The target of this activity is 30 micro and small entrepreneurs who are members of the Prima Danarta Surabaya Credit Union. The participants enthusiastically asked questions, especially about how to search for brands and register trademarks